Geographies of brain culture: optimism and optimisation in workplace training programmes. (January 2016) - Pykett, Jessica; Enright, Bryony
This article outlines the strategic alignment of novel modes of emotional and psychological governance characteristic of 'brain culture' with intensified forms of workplace performance management within specifically neoliberal organisational cultures. We introduce the recent emergence of positive psychology-based workplace training programmes in the UK human resources field as a new empirical site for the study of cultural geographies of education. We demonstrate how such programmes promote a culture of optimism and optimal functioning, focussing on the cultivation of positive emotions among individual workers and in workplace cultures. This emphasis on well-being sits somewhat uncomfortably in the context of the global financial crisis, the United Kingdom's recent recession and the diminishing role of the UK state in the provision of welfare, but is wholly concurrent with the neoliberal promotion of 'lifelong learning' and the spread of individualised practices of performance management in the UK workplaces. The article reports on in-depth interviews with trainers and practitioners who variously use positive psychology, mindfulness training and strengths-based competencies in workplaces in the United Kingdom and outlines their connection to the development of positive psychology as a new academic discipline in the United States. In outlining the importance of context for understanding changing workplace cultures and worker subjectivities, a cultural geography analysis of rapid advancements in psychological knowledge provides a useful new perspective on the links between neoliberalism, the behaviour change and happiness 'industries' and brain culture.